2010
DOI: 10.1007/s00221-010-2254-y
|View full text |Cite
|
Sign up to set email alerts
|

Perceived intensity of somatosensory cortical electrical stimulation

Abstract: Artificial sensations can be produced by direct brain stimulation of sensory areas through implanted microelectrodes, but the perceptual psychophysics of such artificial sensations are not well understood. Based on prior work in cortical stimulation, we hypothesized that perceived intensity of electrical stimulation may be explained by the population response of the neurons affected by the stimulus train. To explore this hypothesis, we modeled perceived intensity of a stimulation pulse train with a leaky neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
25
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 35 publications
7
25
1
Order By: Relevance
“…This supports the hypothesis that electrical stimulation parameters are not perceived independently but rather jointly contribute to a unified perception of intensity (Fridman et al, 2010). This would seem to conflict with the classic experiments of Romo et al (Romo et al, 1998) who showed that periodic stimulation of the skin and electrical stimulation of quickly adapting neurons in area 3b were behaviourally indistinguishable (and therefore presumably perceptually equivalent) in non-human primates.…”
Section: Discussionsupporting
confidence: 86%
“…This supports the hypothesis that electrical stimulation parameters are not perceived independently but rather jointly contribute to a unified perception of intensity (Fridman et al, 2010). This would seem to conflict with the classic experiments of Romo et al (Romo et al, 1998) who showed that periodic stimulation of the skin and electrical stimulation of quickly adapting neurons in area 3b were behaviourally indistinguishable (and therefore presumably perceptually equivalent) in non-human primates.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, there were slight variations in the lengths of the four electrodes used to make each electrode array, potentially resulting in slight depth variations. It should be noted that previous studies have also noted variations in thresholds across animals of a similar order of magnitude [33,47,48]. We also noted a small but nonsignificant decrease in response time with increasing stimulus strength with both symmetric and asymmetric stimuli (data not shown).…”
Section: Discussionsupporting
confidence: 81%
“…There is a suggestion by Fridman et al that ICMS amplitude, pulse-width, and frequency all interact to contribute to a unitary perception of “perceived intensity” [46]. Therefore, one might argue that our monkeys discriminated the periodic and aperiodic pulse trains on the basis of their instantaneous peak intensities rather than their temporal patterns.…”
Section: Discussionmentioning
confidence: 92%